Technologies of information through the eyes of children on a digital era - Iacob, I.; Oliveira, A.; Costa, C. (ICERI2016 Proceedings, 2016)
We live in an era of information, a time when technology is more and more used in several areas of our life. In fact, information technologies are increasingly present in the lives of adults, as well as in children's world. For children, technology, digital media and computers are the most common thing, and navigate in the virtual worlds is as natural as interact in social reality. Since the most early age, they easily adopt new technologies to communicate, interact, play, have fun, support their study and learn about all kind of matters. Our study pretended to verify, from children’s perspective, the importance of information and communication technologies (ICT) in their learning and development. In other words, we aimed to know their level of knowledge about ICT, the technologies they use with more frequency and the contexts where they deal with it, and benefits they obtain through ICT, in school and in their personal path. The participants are students (from 3rd to 6th grade), aged between eight and twelve years, from both genders. Data were collected through a questionnaire developed by us, based on a theoretical-conceptual review, and on the results of previous studies. It included questions related to ICT, their personal use and their use at school. Moreover, it also incorporates items focused on how ICT may contribute to their motivation, attention, satisfaction, confidence, creativity and ease of communication and learning. Some of our findings show that majority of children do not have regular access to ICT and the computers are used more for entertainment. However, they consider that computers are important tools for their learning and education. So, this study may contribute to better understand the children`s behaviour concerning ICT, and how they see the virtual worlds. Furthermore, it may also be relevant for teachers, to adapt and revise curricula, as well as for their understanding on how to motivate children to develop their abilities and skills, through the use of ICT.